Outcome of wide local excision in dermatofibrosarcoma protuberans and use of radiotherapy for margin-positive disease - Raashid Hamid; Adil Hafeez; Mohd A Darzi; Inaam Zaroo; Altaf Rasool; Haroon Rashid (Wolters Kluwer Medknow Publications, 2013)
Purpose: Wide local excision (WLE) is the preferred treatment of dermatofibrosarcoma protuberans (DFSP). The aim is to achieve negtive margins. We followed the impact of radiotherapy used postoperatively for both margin-negative and margin-positive DFSP tumors. Materials and Methods: Outcome of treatment of 36 patients of DFSP treated at our hospital was assessed. Thirty patients received radiotherapy postoperatively and six patients received radiotherapy alone. The maximum dimension of the lesion was 15 cm 2 . Patients were followed up for varying periods of time for any recurrence. Results: 10-year actuarial local control rate was determined. Local control was realized in six patients who were treated with radiotherapy alone. 30 patients were treated by radiotherapy and surgery. Out of these 30 patients, there were 6 local failures (failure rate 10%). Actuarial control rate was 82%. The failures were among patients who had positive margins. Conclusion: Radiotherapy is effective, and it decreases the recurrence rate in the treatment of DFSP. It is especially helpful in margin-positive disease. This appears true for patients treated with radiotherapy alone or radiotherapy used postoperatively.